Association between quantitative analyses of periodontal pathogens and the depth of periodontal pockets. Issue 1 (1st January 2020) - He, Jianan; Da, Lyu; Pan, Yining; Tan, Xuanping; Li, Zhitian; Luo, Feiyue; Xie, Weidong; Gu, Dayong
Abstract: The aim of this study was to investigate the association between expressions of five periodontal pathogens ( Actinobacillus actinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg), Tannerella forsythensis (Tf), Treponema denticola (Td) and Prevotella intermedia (Pi) and the periodontal pocket depth (PD) in people suffering from periodontitis. A study of 1164 plaque samples from individuals with periodontitis were conducted by multiplex real-time quantitative fluorescence-polymerase chain reaction to evaluate the PD and loads of five periodontal pathogens. The total bacterial number did not differ significantly between people with different subtypes of periodontitis. However, expression of specific pathogens (Pg, Td, Tf, Pi) showed a significant increase with the development of periodontitis. Expression of Pg, Td and Tf showed close correlation between them as well as with PD. Analyses of receiver operating characteristic curves showed that expression of Pg, Td, Tf and Pi had good potential for grading periodontitis severity. We found a close correlation between the relative expression of Pg, Td and Tf and PD. Measuring expression of target bacteria in the oral cavity could facilitate the understanding of the role of bacteria in periodontitis. Taking the appropriate steps to eliminate these pathogens might aid the prevention of periodontitis development.